53. TUCATINIB VS PLACEBO ADDED TO TRASTUZUMAB AND CAPECITABINE FOR PATIENTS WITH PREVIOUSLY TREATED HER2+ METASTATIC BREAST CANCER (MBC) WITH BRAIN METASTASES (BM) (HER2CLIMB). (4th August 2020) - Lin, Nancy; Murthy, Rashmi; Anders, Carey; Borges, Virginia; Hurvitz, Sara; Loi, Sherene; Abramson, Vandana; Bedard, Philippe; Oliveira, Mafalda; Zelnack, Amelia; DiGiovanna, Michael; Bachelot, Thomas; et al.
Abstract: BACKGROUND: HER2CLIMB (NCT02614794) primary results have been reported previously (Murthy, NEJM 2019). We report results of exploratory efficacy analyses in pts with brain metastases (BM). METHODS: All HER2+ MBC pts enrolled had a baseline brain MRI. Pts with BM were eligible and randomized 2:1 to receive tucatinib (TUC) or placebo, in combination with trastuzumab and capecitabine. Efficacy analyses were performed by applying RECIST 1.1 to the brain based on investigator evaluation. CNS-PFS and OS were evaluated in BM pts overall. Intracranial (IC) confirmed ORR-IC and DOR-IC were evaluated in BM pts with measurable IC disease. After isolated brain progression, pts could continue study therapy until second progression, and time from randomization to second progression or death was evaluated. RESULTS: Overall, 291 pts (48%) had BM at baseline: 198 (48%) in the TUC arm and 93 (46%) in the control arm. There was a 68% reduction in risk of CNS-PFS in the TUC arm (HR: 0.32; P<0.0001). Median CNS-PFS was 9.9 mo in the TUC arm vs 4.2 mo in the control arm. Risk of overall death was reduced by 42% in the TUC arm (OS HR: 0.58; P=0.005). Median OS was 18.1 mo vs 12.0 mo. ORR-IC was higher in the TUC arm (47.3%) vs the control arm (20.0%). Median DOR-IC was 6.8 mo vs 3.0 mo. In pts with isolated brain progression who continued study therapy after local treatment (n=30), risk of second progression or death was reduced by 71% (HR: 0.29), and median time from randomization to second progression or death was 15.9 mo vs 9.7 mo, favoring the TUC arm. CONCLUSIONS: In pts with previously treated HER2+ MBC with BM, TUC in combination with trastuzumab and capecitabine doubled the ORR-IC, reduced risk of IC progression or death by two-thirds and reduced risk of death by nearly half.